Energy characteristics and optimal design of diffuser meridian in an electrical submersible pump. (April 2021) - Yang, Yang; Zhou, Ling; Hang, Jianwei; Du, Danyang; Shi, Weidong; He, Zhaoming
Abstract: Electrical submersible pump (ESP) is widely used as an artificial lifting machinery in the petroleum production and geothermal usage. Its energy efficiency is related to the amount of produced oil and affects the global energy consumption. This study aimed to improve the energy performance of a typical three-stage ESP. Through the combination of Taguchi methods and numerical simulations, the diffuser meridian within ESP was geometrically optimized by setting the head and efficiency under design flow condition as the evaluation index. On the basis of the Bessel curve characteristics, the line patterns of hub and shroud within the ESP diffuser meridian were parameterized to preliminary extract the necessary factors of Taguchi test. Finally, the influence priority of different factors on the optimization was analyzed to guide the subsequent ESP optimization. Comparison of the performance and the internal flow field of models before and after optimization revealed that the Taguchi test is remarkably helpful in optimizing the meridian within ESP diffuser. This work provides new ideas for optimizing the meridian of main hydraulic components within ESPs to achieve higher efficiency and lower energy consuming. Highlights: The energy characteristics of ESP was studied numerically and experimentally. The diffuser meridian of ESP was optimized by the Taguchi methods. The flow field inside diffuser meridian shown remarkable improvement.